2020
DOI: 10.1145/3355395
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Enhanced Interaction with Cultural Heritage

Abstract: Digital technology in museum practice provides new means of interaction with artifacts and collections. In particular, we need interactive installations in order to encourage and stimulate visitors to learn and understand archaeological musical instruments through engagement and active participation: these instruments (i.e., interactive artifacts per se ) are de facto unplayable and inaccessible to visitors, as a consequence of their preservation issues. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Other multidisciplinary work carried out at CSC in the field of computer engineering for musical cultural heritage concerned the enhancement of modern electrophonic instruments (e.g., Studio Fonologia Musicale della RAI di Milano, see Canazza et al 2011) and of historical musical instruments (e.g., a pan flute, cf. Pretto et al 2020). At CSC, a methodology to develop a multimedia installation that communicates and enhances both acoustic and electrophonic instruments by considering their cultural context has been defined.…”
Section: Preservation Of Historical and Modern Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other multidisciplinary work carried out at CSC in the field of computer engineering for musical cultural heritage concerned the enhancement of modern electrophonic instruments (e.g., Studio Fonologia Musicale della RAI di Milano, see Canazza et al 2011) and of historical musical instruments (e.g., a pan flute, cf. Pretto et al 2020). At CSC, a methodology to develop a multimedia installation that communicates and enhances both acoustic and electrophonic instruments by considering their cultural context has been defined.…”
Section: Preservation Of Historical and Modern Instrumentsmentioning
confidence: 99%
“…The interaction model used to provide access to the general public is based on multisensory interplay (visual, auditory, and tactile) that includes both contextual information and a virtual counterpart of the artifact. The methodology includes an adaptation of "design thinking" for interactive museum installations and a deeply interdisciplinary matching design process (Pretto et al 2020).…”
Section: Preservation Of Historical and Modern Instrumentsmentioning
confidence: 99%
“…Efforts persist towards digitizing cultural heritage collections and placing them 'online', for reasons such as the preservation of the original analogue item and education [25] [42]. While research in the area continues to grow, there is still an observed lack of literature that focuses on the theory and methodology of user interaction and experience regarding digital cultural experiences [25].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural heritage scholars study how DCIs might be formed better, faster and with greater accuracy [23][14], while those focusing on UX informed research draw upon research into formal UX practices [46] [20]and ask how we can use DCIs to create more compelling, more valuable, 'better', cultural user experiences [29] [34]. Curators tackle the technical challenges of developing proficiency in, or gaining access to, an eclectic set of technical and artistic skills required to form and display DCIs, all the while working within strict professional deadlines and institutional budgets [42][27] [47]. Meanwhile, visitors can access vast collections of DCIs from their portable devices and personal computers, with each DCI offering the potential for experiences formed from interactions that would simply be impossible with an analogue cultural item.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation